PELATIHAN PENELITIAN TINDAKAN KELAS BAGI GURU SEKOLAH DASAR - Setiawan, Windi; Hatip, Ahmad; Haerussaleh, Haerussaleh; Huda, Nuril; Martono, Boedi (Jurnal Pengabdian Masyarakat Khatulistiwa, 2023)
ABSTRACTClassroom Action Research (PTK) is research that aims to identify learning problems in the classroom so that appropriate solutions are obtained to realize effective learning. PTK has now become a requirement for teacher professional development. However, teachers at SDN Kedungcowek are less capable in making PTK. This prompted the community service team to hold PTK training for teachers at the school. This training consists of three stages, the first stage is planning, at this stage the community service team coordinates with partners, the second stage carries out training, and the third stage, reflection. At this stage, the community service team measures participants' understanding of the training provided. As a result, most participants had a moderate understanding of the PTK training provided by the community service team. This is shown by the majority of teachers choosing a score of 3 for each indicator on the questionnaire distributed after the training.Keywords: teacher, profession, developmentABSTRAKPenelitian Tindakan Kelas (PTK) adalah penelitian yang bertujuan untuk mengidentifikasi masalah pembelajaran di kelas sehingga didapatkan solusi yang tepat untuk mewujudkan pembelajaran yang efektif. PTK kini telah menjadi syarat untuk pengembangan profesi guru. Hanya saja, di guru di SDN Kedungcowek kurang mampu dalam membuat PTK. Hal ini membuat tim abdimas untuk mengadakan pelatihan PTK bagi para guru di sekolah tersebut. Pelatihan ini terdiri dari tiga tahap, tahap pertama yaitu perencanaan, pada tahap ini tim abdimas melakukan kordinasi dengan mitra, tahap kedua melakukan pelatihan, dan tahap ketiga, refleksi. Pada tahap ini, tim abdimas mengukur keterpahaman peserta mengenai pelatihan yang diberikan. Hasilnya, sebagian besar peserta memiliki pemahaman sedang terhadap pelatihan PTK yang diberikan oleh tim abdimas. Hal ini ditunjukkan dari sebagian besar guru memilih skor 3 untuk setiap indikator pada angket yang dibagikan seusai pelatihanKata Kunci: guru, profesi, pengembangan